Efektivitas Model Pembelajaran NHT (Numbered Heads Together) dalam Meningkatkan Keaktifan dan Hasil Belajar Siswa MTs Negeri 8 Kebumen - Salimah, Siti (QuranicEdu: Journal of Islamic Education, 2024)
This research aimed to increase student activity and learning outcomes by implementing the Numbered Heads Together (NHT) cooperative learning model. This research was conducted using the PTK (Classroom Action Research) method with 2 cycles. Each cycle was carried out in four stages, namely planning, implementation, observation and reflection. The subjects of this research were 34 students in class VIII E MTs N 8 Kebumen. The results of the research showed that student activity in the learning process increased pre-cycle by 15%, cycle 1 by 64.88% and cycle 2 by 81.99%. The average student score in pre-cycle was 62.65, in cycle 1 it was 72.06 and in cycle 2 it was 77.06. Students experienced learning completeness with scores above the KKM in the pre-cycle of 15%, cycle 1 of 68% and cycle 2 of 91%. Based on these results, this PTK research could be said that the application of the Numbered Heads Together (NHT) type cooperative learning model could increase student activity and learning outcomes.